PENGGUNAAN MEDIA SOSIAL DALAM PERSPEKTIF TAFSIR AL-MISBAH BERDASARKAN QS. AN-NAHL [16]: 90 DAN QS. AL-HUJURAT [49]: 6 SEBAGAI ETIKA BERKOMUNIKASI DAN BERINTERAKSI DI ERA DIGITALISASI - Muhammad Halif Asyroful Bahana (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2023)
Technological advancements in the digital era have significantly transformed the way people communicate and interact, particularly through social media. However, the irresponsible use of social media can lead to negative consequences, such as misinformation, hate speech, and social division. Therefore, ethical guidelines are essential to ensure proper communication and interaction in the digital space. This study examines the perspective of Tafsir Al-Misbah on ethical principles of communication and interaction on social media based on QS. An-Nahl [16]: 90 and QS. Al-Hujurat [49]: 6. The research employs a literature review method with a thematic tafsir approach. The findings indicate that QS. An-Nahl [16]: 90 highlights justice, kindness, and compassion as fundamental principles of communication, while QS. Al-Hujurat [49]: 6 emphasizes the importance of tabayyun (verification) before disseminating any information. Tafsir Al-Misbah provides insights into how these verses serve as key guidelines for social media engagement, fostering more respectful, harmonious, and responsible communication